Carbonaceous schists of the Main Central Thrust zone as a source of graphite: a case study from the Kali Gandaki valley, west Nepal - Paudel, Lalu Prasad (Bulletin of the Department of Geology, 2011)
Petrological study and X-ray diffraction analysis were carried out to identify the content and quality of graphitic material inthe carbonaceous schist from the Main Central Thrust zone in the Kali Gandaki valley, west Nepal. The study shows that thecarbonaceous schists contain more than 15-30% graphite. They contain both amorphous and flake graphite with variable grainsize. As graphite is being mined commercially in rocks containing even <5% graphite worldwide, carbonaceous rocks of the MainCentral Thrust zone can be a potential sources of commercial graphite in Nepal. DOI: http://dx.doi.org/10.3126/bdg.v14i0.5431 Bulletin of the Department of Geology Vol.14 2011, pp. 9-14